Promising Therapeutic Candidate for Myocardial Ischemia/Reperfusion Injury: What Are the Possible Mechanisms and Roles of Phytochemicals? - Chen, Cong; Yu, Lin-Tong; Cheng, Bai-Ru; Xu, Jiang-Lin; Cai, Yun; Jin, Jia-Lin; Feng, Ru-Li; Xie, Long; Qu, Xin-Yan; Li, Dong; Liu, Jing; Li, Yan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Percutaneous coronary intervention (PCI) is one of the most effective reperfusion strategies for Acute myocardial infarction (AMI) despite myocardial ischemia/reperfusion (I/R) injury causing one of the causes of most cardiomyocyte injuries and deaths. The pathological processes of myocardial I/R injury include apoptosis, autophagy and irreversible cell death caused by calcium overload, oxidative stress, and inflammation. Eventually, myocardial I/R injury myocardial I/R injury causes a spike of further cardiomyocyte injury that contributes to final infarct size (IS) and bound with hospitalization of heart failure as well as all‐cause mortality within the following 12 months. Therefore, the addition of adjuvant intervention to improve myocardial salvage and cardiac function call for further investigation. Researchers have put great effort into phytochemicals because they are often in line with the expected standards, that is, to improve myocardial I/R injury without compromising the clinical efficacy or to even produce synergy. Phytochemicals are non-nutritive bioactive secondary compounds abundantly found in Chinese herbal medicine. We summarized the previous efforts, briefly outlined the mechanism of myocardial I/R injury, and focused on exploring the cardioprotective effects and potential mechanisms of all phytochemical types that have been investigated under myocardial I/R injury. Phytochemicals deserve to be utilized as promising therapeutic candidates for further development and research in combating myocardial I/R injury. Nevertheless, more studies are needed to provide a better understanding of the mechanism of myocardial I/R injury treatment using phytochemicals and possible side effects associated with this approach.